2011
DOI: 10.1159/000328160
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Stress-Induced Immunomodulation on Th1/Th2 Cytokine and Catecholamine Receptor Expression in Human Peripheral Blood Cells

Abstract: Aims: There is evidence that psychological stress can modulate immune functions. It has been hypothesized that acute stressors can affect both immune balance (including Th1 and Th2 cytokines) and expression of stress hormone receptors. This study investigated the impact of an acute stressor on gene expressions of glucocorticoid receptor (GR), and β2-adrenergic receptor (β2AR) in leukocytes. The effect on T regulatory cells (Treg), regulatory cytokines IL-10 and TGF-β, Th1 and Th2 cytokines and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 70 publications
(36 reference statements)
1
18
0
Order By: Relevance
“…These facts support that in mediating the CA immunomodulation, α 1 -ARs and β 2 -ARs play a dominant role. Several studies, including that from our laboratory, have demonstrated the presence of AR subtypes on immunocytes and their various functions in mediating immunomodulation of CAs [23,24,25,29,30,31,44]. Thus, a possible mechanism underlying the modulation of lymphocyte differentiation and function by the lymphocyte-derived CAs is established.…”
Section: Discussionmentioning
confidence: 97%
“…These facts support that in mediating the CA immunomodulation, α 1 -ARs and β 2 -ARs play a dominant role. Several studies, including that from our laboratory, have demonstrated the presence of AR subtypes on immunocytes and their various functions in mediating immunomodulation of CAs [23,24,25,29,30,31,44]. Thus, a possible mechanism underlying the modulation of lymphocyte differentiation and function by the lymphocyte-derived CAs is established.…”
Section: Discussionmentioning
confidence: 97%
“…As Xiang reported, acute stressor augmented the production of Th1 cytokine in normal volunteers through the protective immune response. 25 Stress and anxiety enhanced late-phase responses and promoted hyperresponsiveness in patients with allergic rhinitis. 43 Cohen et al 44 found that chronic psychological stress dysregulated the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…22 Neuroimmunology of psychological symptoms is dominated by "immune activation" hypothesis and "immune suppression" hypothesis. 23 The balance of Th cells is shifted toward Th1 cells 24,25 and Th17 cells 26,27 in depression or anxiety.…”
mentioning
confidence: 99%
“…Data on the effects of different types of stress on Tr1 cells are also limited. We recently reported that the percentage of Tr1 cells is lower 2 h after administration of an acute psychological stressor in a human stress model [43]. Th3 cells produce TGFβ, which is an important factor in the differentiation of regulatory cell phenotypes, including classic FoxP3 + regulatory T cells (Treg) and Th17 cells [44].…”
Section: Discussionmentioning
confidence: 99%